30 years of data reveal dramatic increase in abundance of brown trout following the removal of a small hydrodam. (15th December 2017) - Birnie-Gauvin, Kim; Larsen, Martin H.; Nielsen, Jan; Aarestrup, Kim
Abstract: Humans and freshwater ecosystems have a long history of cohabitation. Today, nearly all major rivers of the world have an in-stream structure which changes water flow, substrate composition, vegetation, and fish assemblage composition. The realization of these effects and their subsequent impacts on population sustainability and conservation has led to a collective effort aimed to find ways to mitigate these impacts. Barrier removal has recently received greater interest as a potential solution to restore river connectivity, and reestablish high quality habitats, suitable for feeding, refuge and spawning of fish. In the present study, we present thirty years of data from electrofishing surveys obtained at two sites, both prior to and following the removal of a small-scale hydropower dam in Central Jutland, Denmark. We demonstrate that the dam removal has led to a dramatic increase in trout density, especially in young of the year. Surprisingly, we found that this increase was not just upstream of the barrier, where the ponded zone previously was, but also downstream of the barrier, despite little changes in habitat in that area. These findings suggest that barrier removal may be the soundest conservation option to reinstate fish population productivity. Highlights: We evaluated brown trout density prior to and following the removal of a small dam in Denmark for 30 years. We show that brown trout density increased dramatically following removal, especially for young of the year. We also show that brown trout density increased both upstream and downstream of where the barrier was previously. Our results illustrate how barrier removal may promote the sustainability and conservation of fish populations.